1998
DOI: 10.1016/s0092-8674(00)81641-4
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Regulatory Circuitry of a Eukaryotic Genome

Abstract: Genome-wide expression analysis was used to identify genes whose expression depends on the functions of key components of the transcription initiation machinery in yeast. Components of the RNA polymerase II holoenzyme, the general transcription factor TFIID, and the SAGA chromatin modification complex were found to have roles in expression of distinct sets of genes. The results reveal an unanticipated level of regulation which is superimposed on that due to gene-specific transcription factors, a novel mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

95
1,725
5
8

Year Published

1999
1999
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,689 publications
(1,833 citation statements)
references
References 65 publications
95
1,725
5
8
Order By: Relevance
“…The high transcription of enzymes involved in highly active pathways during fermentation (and possibly not during aerobic respiration) correlates particularly well with the high CAI value of these enzymes. This observation is supported also by the available transcriptomic data on seripauperine proteins (Holstege et al 1998;James et al 2003;Viswanathan et al 1994) and on Hem13 proteins (Amillet et al 1995).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…The high transcription of enzymes involved in highly active pathways during fermentation (and possibly not during aerobic respiration) correlates particularly well with the high CAI value of these enzymes. This observation is supported also by the available transcriptomic data on seripauperine proteins (Holstege et al 1998;James et al 2003;Viswanathan et al 1994) and on Hem13 proteins (Amillet et al 1995).…”
Section: Introductionsupporting
confidence: 67%
“…Transcriptomic data for S. cerevisiae are taken from the study reported by Holstege et al (1998) and based on Affymetrix GeneChip high-density oligonucleotide array (HDA) technology (downloaded from http://www.wi.mit.edu/young/expression.html in 1999, and Table 1, Mycobacterium tuberculosis H37Rv (mtbrv), and Helicobacter pylori (hpy). For each organism, the RPI value associated with a pathway, if it exists, is indicated by the corresponding ranking color.…”
Section: Transcriptomic Data and Expression Levelsmentioning
confidence: 99%
“…The distributions of mRNA concentration in the three strains were compared by means of the matched pair t-test, the non-parametric sign test and the non-parametric Wilcoxon signed-rank test, which always rendered p values < 0.0001. A strong correlation between the mRNA levels in the three strains was observed, and also with the mRNA levels from Holstege et al (1998), which are widely considered to be accurate absolute gene expression-level data (Table 2).…”
Section: Genechip Expression Analysismentioning
confidence: 67%
“…Unexpectedly, initial studies revealed that the mutation or depletion of seven TAF II s individually resulted in gene-specific defects, and not global reductions in transcription Moqtaderi et al, 1996;Walker et al, 1996). In contrast, genetic analysis of other TFIID subunits that have sequence similarities to the core histones has shown that they are required for the transcription of a larger number of genes (Apone et al, 1998;Holstege et al, 1998;Michel et al, 1998;Moqtaderi et al, 1998;Natajaran et al, 1998;Sanders et al, 1999;Reese et al, 2000). The interpretation of these results is complicated by the presence of certain TAF II s in the SAGA histone acetyltransferase complex (Grant et al, 1998), and their function in multiple complexes may partially explain the expanded requirement for these TAF II s in transcription (Lee et al, 2000).…”
Section: Introductionmentioning
confidence: 99%